2022
DOI: 10.1590/2177-6709.27.5.e2220448.oar
|View full text |Cite
|
Sign up to set email alerts
|

Dentoalveolar changes observed after the use of customized bonded Shark-Tooth-Like Spurs (JAWs) in adult patients with anterior open bite

Abstract: Introduction: Tongue spurs have been successfully used for the early treatment of anterior open bite (AOB). However, according to our knowledge, their effectiveness in the treatment of adults has not been evaluated. Objectives: The purpose of the study was to assess the dentoalveolar changes observed after the use of customized bonded shark-tooth-like spurs (JAWs) in adults with AOB. Methods: Twenty-three adults (22.1±4.4 years) with AOB were selected for the treatment. JAWs made from compomer cement were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…These results were consistent with those of Atout et al, 21 Kim et al, 8 de Brito Vasconcelos et al, 15 and Kraisiridej et al 22 Regarding the effect of the extrusion arch on dental arches parameters, the results of the current study showed that the upper arch length and the upper arch perimeter reduced significantly by 2.09 ± 0.76 mm and 1.9 ±0.87 mm, respectively, with no significant change in the lower arch length and perimeter. These results were similar, but they were greater in magnitude, to those of Aliaga-Del Castillo et al 23 the incisors palatally; while the tongue spurs or crib depends on change in the muscle equilibrium, tending to pure extrusion of the upper incisors.…”
Section: Resultssupporting
confidence: 92%
“…These results were consistent with those of Atout et al, 21 Kim et al, 8 de Brito Vasconcelos et al, 15 and Kraisiridej et al 22 Regarding the effect of the extrusion arch on dental arches parameters, the results of the current study showed that the upper arch length and the upper arch perimeter reduced significantly by 2.09 ± 0.76 mm and 1.9 ±0.87 mm, respectively, with no significant change in the lower arch length and perimeter. These results were similar, but they were greater in magnitude, to those of Aliaga-Del Castillo et al 23 the incisors palatally; while the tongue spurs or crib depends on change in the muscle equilibrium, tending to pure extrusion of the upper incisors.…”
Section: Resultssupporting
confidence: 92%
“…Suzuki en el 2022 en su estudio nos dice que se produjeron cambios dentoalveolares después del primer mes de tratamiento con JAW (espolones linguales) se produjo una retro inclinación de los dientes anteriores que combinada con la expansión de los dientes posteriores sugiere un cambio posterosuperior en la posición de la lengua. Estos cambios fueron beneficiosos para el tratamiento de la AOB en pacientes adultos (18).…”
Section: Discussionunclassified
“…Часто даний вид патології поєднується з аномаліями в сагітальній площині [3,4]. Визначено, що ефективність діагностики і лікування пацієнтів з функціональними розладами зубо-щелепного апарату, поєднаних з денто-альвеолярною формою глибокого прикусу, залишається вагомою проблемою сучасної стоматології.…”
Section: вступunclassified